Contribution of mashua to the social welfare of potato producers through control of the Andean potato weevil (GnosisWisdom, 2025)
The ‘Andean weevil’ is one of the main pests affecting potato crops in the high Andean regions of Peru and South America, but fortunately, mashua can be used as a living barrier to control this pest. The objective was to analyse the scientific evidence on the use of mashua as a living barrier to control the Andean weevil. Scientific literature published between 2020 and 2025 on the repellent and allelopathic potential of mashua against this Andean weevil was reviewed. The results highlight that, thanks to the content of glucosinolates and isothiocyanates in mashua, the incidence of the weevil is reduced by altering its oviposition behaviour, although the effectiveness of this strategy depends on factors such as altitude, crop system design, and barrier density. While its use promotes sustainability, further research is still needed to validate its efficacy, characterise its active metabolites, and optimise its control in diverse contexts. Among the conclusions, it is highlighted that the use of mashua represents a promising agroecological alternative for the control of the Andean weevil in potato crops, thanks to its repellent and biofumigant properties.
Keywords: Tropaeolum tuberosum; Premnotrypes sp; pests; control